IDENTIFIKASI DAYA TARIK WISATA PURA GUNUNG PANGSUNG DI PULAU LOMBOK - Anggreni, Ni Luh Eka Yuli (Institut Agama Hindu Negeri Gde Puda Mataram, 2024)
Lombok Island has a panorama of natural beauty and an extraordinary unique and diverse culture. One example is the variety of religious-based tourism, so temples are very suitable to become cultural tourism objects. The research method in this study used descriptive qualitative research techniques. argues about the phenomenon of cultural tourism, using a phenomenological research approach, which examines the Gunung Pangsung Temple Cultural Tourism Object which aims to reveal the existence and position of the Gunung Pangsung Temple Cultural Tourism Object. Data collection techniques using direct observation and interviews as well as documents in the form of photos. The presentation of the data results uses a narrative presentation, which is described in accordance with the data and facts in the field. The results of the study are as follows: The existence of the Gunung Pangsung Temple Cultural Tourism Object can be seen through the environment and also the spiritual. The position of the Gunung Pangsung Temple Cultural Tourism Object is categorized as still very sacred, it can be seen from the history of the Gunung Pangsung Temple, the rules that exist at the Gunung Pangsung Temple and the spiritual experience of the stakeholders as well as from the community or pemedek who are fighting.